2008
DOI: 10.1093/aob/mcn074
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear DNA Microsatellites Reveal Genetic Variation but a Lack of Phylogeographical Structure in an Endangered Species, Fraxinus mandshurica, Across North-east China

Abstract: The modern genetic structure in this species can be explained by extensive gene flow, an absence of mountains acting as barriers, and the presence of a wide refuge across NEC rather than multiple small refugia. Intra-population genetic variation along latitudes is probably associated with the systematically northward shifts of forest biomes in eastern China during the mid-Holocene. To determine important genetic patterns and identify resources for conservation, however, it will be necessary to examine differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
68
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 50 publications
7
68
0
Order By: Relevance
“…In European studies of F. excelsior based on nSSR loci (Morand et al 2002;Heuertz et al 2001;FRAXIGEN 2005;Ferrazzini et al 2007), it was found that genetic diversity within populations and allelic richness were high. The same observation was reported for F. mandshurica in northeast China (Hu et al 2008). Moreover, two contrasting patterns of within and among population diversity between western and southern European populations of common ash have been observed (Heuertz et al 2004b;Ferrazzini et al 2007).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In European studies of F. excelsior based on nSSR loci (Morand et al 2002;Heuertz et al 2001;FRAXIGEN 2005;Ferrazzini et al 2007), it was found that genetic diversity within populations and allelic richness were high. The same observation was reported for F. mandshurica in northeast China (Hu et al 2008). Moreover, two contrasting patterns of within and among population diversity between western and southern European populations of common ash have been observed (Heuertz et al 2004b;Ferrazzini et al 2007).…”
Section: Discussionsupporting
confidence: 81%
“…Negative correlations of the genetic diversity with geographical gradients have been observed in F. mandshurica populations of NE China (Hu et al 2008). No evidence of correlation between geographical distance and genetic differentiation of the population studied was observed.…”
Section: Discussionmentioning
confidence: 73%
“…Similar results were also found for other wind-pollinated long-lived plants such as Fraxinus mandshurica Rupr. by Hu et al (2008).…”
Section: Phylogeography and Migration Routesmentioning
confidence: 93%
“…for the argan forest based on alloenzymes (Fst=0.24) (El Mousadik and Petit, 1996) and based on ISSR markers (Gst= 0.40) (Mouhaddab et al, 2015) and (Gst= 0.39) (Yatrib et al, 2015). Compared to other deciduous woody plants with similar geographical distribution such as Fraxinus mandshrurica (He= 0.564; Fst= 0.010) (Hu et al, 2008), Acer mono (He= 0.737, Fst= 0.073) (Liu et al, 2014), the argan tree is considered as one of the most genetically differentiated forest resources. Hamrick et al, (1992) has reviewed plant alloenzymes literature in plant species, summarizing parameters of genetic diversity, with special attention to trees.…”
Section: Discussionmentioning
confidence: 99%